2017
DOI: 10.1016/j.nicl.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Localizing value of electrical source imaging: Frontal lobe, malformations of cortical development and negative MRI related epilepsies are the best candidates

Abstract: ObjectiveWe aimed to prospectively assess the anatomical concordance of electric source localizations of interictal discharges with the epileptogenic zone (EZ) estimated by stereo-electroencephalography (SEEG) according to different subgroups: the type of epilepsy, the presence of a structural MRI lesion, the aetiology and the depth of the EZ.MethodsIn a prospective multicentric observational study, we enrolled 85 consecutive patients undergoing pre-surgical SEEG investigation for focal drug-resistant epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
5
25
0
2
Order By: Relevance
“…Simultaneous scalp and SEEG studies also proved that IID recorded in scalp electrodes could match with inter-ictal activity generated in cortical areas related to but outside of the EZ (Alarcon et al 1994;Koessler et al 2015). In previous ESI studies, we also demonstrated that localizing sources from IID encompasses a significant risk of localizing outside the EZ (Rikir et al 2014;Abdallah et al 2017).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Simultaneous scalp and SEEG studies also proved that IID recorded in scalp electrodes could match with inter-ictal activity generated in cortical areas related to but outside of the EZ (Alarcon et al 1994;Koessler et al 2015). In previous ESI studies, we also demonstrated that localizing sources from IID encompasses a significant risk of localizing outside the EZ (Rikir et al 2014;Abdallah et al 2017).…”
Section: Introductionsupporting
confidence: 70%
“…to standard pre-surgical evaluation (Knowlton et al 2009;Beniczky et al 2013;Rikir et al 2014;Abdallah et al 2017). Most of them used inter-ictal discharges (IID) for source localization (Gavaret et al 2004(Gavaret et al , 2006(Gavaret et al , 2009Brodbeck et al 2011) because these discharges are easier to record during a limited period of time, have a higher signal-to-noise ratio (SNR), and are less susceptible to be contaminated by muscle and movement artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Of 20 cases of normal or non‐localizable II‐EEG, IC‐ESI could correctly localize the source in 11 patients who became seizure‐free after surgery. Concordance between ESI and ICR was 52–72%, consistent with previous studies (60–82%) . In our series, concordance with ICR results was best for II‐ECD (72%).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting target for future research would be to investigate (and compare to MSI results) electric source imaging (ESI) specifically for FCD II, including high-density EEG (HD-ESI). Some studies using ESI for localizing diagnostics for epilepsy surgery did include FCD patients ( Abdallah et al, 2017 , Russo et al, 2016 , Lascano et al, 2016 , Rikir et al, 2014 , Brodbeck et al, 2011 ). From these reports, that did include quite heterogenous etiologies, it seems that ESI can be particularily successful in FCD II-related epilepsies.…”
Section: Discussionmentioning
confidence: 99%